FUNCTIONAL ANALYSIS AND FUNCTIONAL MAPS OF QUALIFICATIONS IN ECVET CONTEXT - V. A. Kopnov; O. V. Shmurygina; D. E. Shchipanova; M. A. Dremina; L. Papaloizou; Y. Orphanidou; P. Morevs (Russian State Vocational Pedagogical University, 2018)
Introduction. Activation of the process of internationalisation and mobility in Russian Vocational Education and Training (VET) is quite possible by adapting principles and methodology of the European Credit Transfer System for Vocational Education and Training (ECVET). The need to achieve transparency of qualifications, recognition of learning outcomes in view of achieving qualifications, accumulation, comparison and transfer of learning outcomes becomes more apparent and urgent for integration processes of VET systems in Russia and European Union countries and is currently under consideration by the RUECVET project team.The aimis to adjust application of functional analysis to description of an occupation in terms of work functions with the following conversion of the defined functions into sets of learning outcomes necessary for characterizing a qualification. The ECVET principles and technical specifications form the context of the research in order to develop an adequate VET study programme for achieving the correspondent qualification of level 4 or 5 of the European Qualifications Framework (EQF) in the Russian education environment. Methodology and research methods. The methodology is based on the functional analysis of an occupational sector and the functions performed within it in such a manner that the following identification of the correspondent units of learning outcomes for the relevant qualification can be fulfilled. The research has been conducted by means of the content-analysis, modelling and expert estimation method.Results and scientific novelty. Comparative analysis of approaches to the design of occupations and qualifications in both national and European environments is presented in the article. The functional analysis is used for allocation of work functions and creation of units of learning outcomes related to a particular qualification. The procedure of applying functional analysis to an occupation as well as the technology of consequent construction of the functional map for the correspondent qualification taking into account the relevant educational and occupational standards and sectoral preferences have been elaborated. The result of the study is adaptation of methodology of functional analysis and verification of the developed procedure when constructing a functional map of the chosen qualification. The procedures are illustrated on the qualification of a lawyer achieved in the VET study programme "Legislation and Social Protection", equivalent to level 5 of the European Qualifications Framework (EQF). Successful experiments with occupations of welders, electricians, web designers, hospitality managers and others related to the qualifications of level 4 and 5 of EQF have been also completed in RUECVET project, although are not described in the article due to the restricted volume.Practical significance. The derived procedures are useful for development of a set of detailed learning outcomes from functional mapping by allocating knowledge and skills and using the concept of unit of learning outcomes for compilation of a qualification in accordance with the relevant educational and occupational standards and employers' understanding how the real work should be performed. The procedures are useful also for identifying units of learning outcomes to build an adequate VET study programme in ECVET context of Russian educational system.